A new geometric modeling of modified magnetic particles with the energy flow and power - Korpinar, Talat; Korpinar, Zeliha; Rezazadeh, Hadi; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2021)
In this study, we firstly characterize modified magnetic particles and associated magnetic fields by considering the evolution of the charged particle together with its modified frame construction in 3D space. Then, we compute the energy flows of each modified magnetic particles in terms of its curvature and torsion in the space. Finally, we obtain energy flux density, the intensity of the light, power of modified magnetic particles in the space.
Keywords: Magnetic field; force field; energy; modified frame; magnetic force